Peraturan Presiden No.36 Tahun 2005 Tentang Pengadaan Tanah Bagi Pelaksanaan Pembangunan Untuk Kepentingan Umum Sebagai Aktualisasi Hak Menguasai dari Negara Atas Tanah di Indonesia - Mezak, Meray Hendrik (Pelita Harapan University, 2005)
As the Presidential Regulation or Peraturan Presiden abbreviated Perpres Number 36 of 2005 on Land Availability for Public Usage came into force many academics, scholars in agrarian law and even public showed a broad resistance and rejection. This is, of course, intersting to study since land is the primary necessity (footstool) of every human being. Such necessity needs government protection. How far the government has already supplied the citizens with adequate (legal) protection and land management is the focus Â of this study.